PARENTING KESEHATAN DIRI DAN LINGKUNGAN: PENTINGNYA GIZI BAGI PERKEMBANGAN ANAK - Wulandari, Yuwinda; Apriyanti, Liana; Meiyansari, Monika; Nurhasanah, Nurhasanah; Putri, Yecha Febrieantha (Jurnal Multidisipliner Bharasumba, 2022)
This research is entitled The importance of personal and environmental health: The importance of nutrition for child development. This article discusses personal and environmental health and the importance of nutrition for child development. The purpose of this article is to find out what personal and environmental health is and the importance of nutrition for child development. Health can be defined as a state of complete physical, mental and social well-being and not simply the absence of disease or infirmity. The environment itself can be interpreted as a space where humans move in order to carry out social activities that involve all aspects of the room in accordance with the instincts of human needs that drive the power of related human social activities. Nutrition is one of the factors that are absolutely necessary in the process of physical growth and development, the nervous system and brain, as well as the level of intelligence and human intelligence. Fulfillment of nutritional needs (nutrients) is the main factor to achieve growth and development results in accordance with genetic potential.